Genetic variation of the mitochondrial genes, CO1 and ND5, in aedes aegypti from various regions of Peninsular Malaysia - Yugavathy, N.; Kim-Sung, L.; Joanne, S.; Vythilingam, I. (Malaysian Society for Parasitology, 2016)
Aedes aegypti is the primary vector of dengue viruses in many parts of the world. In peninsular Malaysia, epidemics of dengue occur more at certain sites particularly in the west central region compared to the eastern region. In this study, we determined the genetic diversity of Ae. aegypti collected from 19 localities in 5 regions of peninsular Malaysia based on two mitochondrial DNA genes; CO1 and ND5. The total number of haplotypes obtained for CO1 and ND5 gene were 14 (C1-C14) and five (N1-N5), respectively. Haplotype genealogical network constructed using concatenated CO1-ND5 gene sequences revealed 18 haplotypes (H1-H18) that were separated into two distinct lineages. Phylogenetic analysis showed that the first lineage (C11 and C3) was more closely related to those from Brazil and France. Unique low frequencies haplotypes detected in the current sampling was closely related to those previously found in India, Pakistan and Vietnam samples, suggesting recent invasion of these haplotypes through human movement or transportation. This is the first study in Malaysia which serves as an initial preliminary phase for a much larger study throughout the country. The understanding of the population diversity of Ae. aegypti and its impact on dengue transmission will be essential for planning of effective control programmes to reduce the burden of dengue.